Self-reported beta-lactam intolerance: not a class effect, dangerous to patients, and rarely allergy. Issue 6 (3rd June 2019) - Vyles, David; Macy, Eric
ABSTRACT: Introduction : About 8% of the United States population carries an unconfirmed penicillin 'allergy' in their medical record. Many physicians needlessly avoid other beta-lactam use in individuals with unconfirmed penicillin allergies. There is a significantly increased risk of developing serious antibiotic-resistant infections, and increased morbidity and mortality in those who report penicillin allergy. Areas covered : Within this study, we reviewed the relevant literature on self-reported beta-lactam allergy. We discuss how the myth of serious allergy to penicillin developed and then discuss and in detail clinically significant immunologically mediated hypersensitivity reactions. Following this discussion, we delineate the risks of not using a beta-lactam when it is the drug of choice and then discuss the epidemiology of beta-lactam-associated anaphylaxis, serious cutaneous adverse reactions, and serious systemic immunologically mediated reactions. Following these topics, we further discuss the consensus current best practices to de-label patients with reported penicillin allergy. Expert opinion : An unconfirmed allergy to penicillin offers considerable harm to patients. Many patients have low-risk allergy symptoms to penicillin who could likely tolerate the medication without having an allergic reaction. The current best practices to de-label reported penicillin allergy is the utilization of a single dose oral challenge, with 1 h of observation, in low-risk patients.